Search, Flows, Job Creations and Destructions - Pierre Cahuc (Institute for the Study of Labor (IZA), 2014)
This paper presents a short overview of dynamic models of labor markets with transaction costs. It shows that these models have deeply renewed the understanding of job search, job flows, job creations and destructions, unemployment and wage formation. It argues that this renewal provides a very useful toolkit for analyzing important economic policy issues such as the optimal level of unemployment benefits, the funding of unemployment insurance and the impact of employment protection legislation.
Keywords: J6; J31; J38; 330; job search; job flows; workers flows; unemployment